Producción, comercialización y rentabilidad de la yuca (manihot esculenta) y su relación con la economía del cantón La Maná y su zona de influencia, año 2011 - Cajas Robles, Claribel Angélica (2014)
The project is focused on the production, marketing and profitability of cassava which is grown in La Maná canton because most of the inhabitants are dedicated to agriculture. It is important to mention that the inhabitants cultivate different products such as cassava, cocoa, coffee, oranges, and so on. An executed study to a particular group showed that there are 38 producers and 20 intermediaries in La Maná canton. Surveys were applied in order to obtain real data of distributors....